Sistem Rekomendasi Tempat Wisata di Provinsi Riau dengan Metode Simple Additive Weighting (SAW) - Risky Silitonga; Yelfi Vitriani; Elin Haerani; Fitra Kurnia (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Riau is a province that has quite good potential for new tourist attractions and tourist destinations that can be developed further. Because there are quite a lot of tourist attractions in Riau, it is difficult for the community to choose recommendations for tourist attractions that suit the wishes of the user. Therefore, the researcher created a recommendation system to assist the community in choosing the tourist attractions they want to visit. In developing this recommendation system, the Simple Additive Weighting method is used, where this method ranks alternative tourist destinations according to predetermined criteria values. The criteria offered by the system are distance, cost, facilities, time and accessibility. The system created can help people to choose the right tourist destination. Web-based built system. The recommendation system for tourist attractions in Riau Province with the Simple Additive Weighting method has succeeded in assisting users in selecting tourist attractions according to predetermined criteria values. Then the best recommendation for tourist attractions on behalf of Ulo Kasok tourist attractions is obtained with the final result value ( 88.80), Based on the UAT test, the results obtained were 83%, which means that the user really agreed